Effective sugar-derived organic gelator for three different types of lubricant oils to improve tribological performance - Zhang, Ruochong; Liu, Xuqing; Guo, Zhiguang; Cai, Meirong; Shi, Lei (Friction, 2020)
In this study, the gelling ability and lubrication performance of N-octadecyl-D-gluconamides (NOG) in liquid paraffin (LP), pentaerythritol oleate (PE-OA), and polyethylene glycol (PEG) oils were systemically investigated. The NOG, which could gelate the investigated oils, was successfully synthesized by a one-step method. The prepared gel lubricants were completely thermoreversible and exhibited improved thermal stability, according to the thermogravimetry analysis (TGA) reports. Rheological tests confirmed that the NOG gelator could effectively regulate the rheological behavior of the base oils. Tribological evaluation suggested that NOG, as an additive in the three types of base oils, could remarkably reduce the friction and wear in steel contacts. A plausible mechanism for the improved performances was proposed based on the mechanical strength of the gels and the formation of the boundary-lubricating film on the worn surface. The results indicated that NOG is a potential gelator for preparing gel lubricants with excellent tribological properties and environment-friendly characteristics.